?DEVELOPMENT OF CATALYST FROM NATURAL CLAYS FOR FRIEDEL CRAFTS ALKY- LATION AND NEW SYNTHESIS OF 9,10 DIHYDROANTHRACENE (Biological Sciences - PJSIR, 1999)
Catalytic activityofthenaturalkaoliniticclaysofPakistancontainingtransitionmetals(FeandTi) hasbeenexamined for the synthesis of 9, 10 dihydroanthracene [I]. The chemical composition of these clays has been determined with and without activation andXRF analysis hasbeencarriedout. Catalyticactivityoftheseclayshasalso beenevaluated for the synthesis of 9, 10dihydroanthracene [I] of low temperature (60-100°C),This method has been standardised, which is a simple method as compared to the methods reported in the literature, The benzylation of phenol with benzyl chloride, resulting in the [ormation of ortho [lI]and para [Ill] hydroxydiphenyl methaneproceeds very smoothly in the water bath to yield 100%of the product. Clays containing (Ti) and Fe) are most effective for the alkylation with benzyl chloride, Leachingofalkalinecationsresultsinthegenerationoflarge amountoftransitionmetalcations,This improvesthecatalytic effect of the acid treated clays,